5-minute Fancy Nancy stories - O'Connor, Jane; Preiss-Glasser, Robin (New York, NY HarperFestival, an imprint of HarperCollins Publishers, 2015)
A collection of twelve previously-published stories in which Fancy Nancy visits the aquarium, discovers her family history, and more
Fancy Nancy and the late, late, late night -- Fancy Nancy: hair dos and hair don'ts -- Fancy Nancy and the too-loose tooth -- Fancy Nancy and the mean girl -- Fancy Nancy: sand castles and sand palaces -- Fancy Nancy: budding ballerina -- Fancy Nancy: the 100th day of school -- Fancy Nancy: pajama day -- Fancy Nancy: my family history -- Fancy Nancy: spring fashion fling -- Fancy Nancy and the boy from Paris -- Fancy Nancy: peanut butter and jellyfish
English stories
Ages 4-8
2
Keywords: Fancy Nancy -- (Fictitious character) -- Juvenile fiction; Vocabulary -- Fiction; Fiction; Juvenile works; Short stories